2020
DOI: 10.1038/s41593-020-0623-9
|View full text |Cite
|
Sign up to set email alerts
|

Primate auditory prototype in the evolution of the arcuate fasciculus

Abstract: The human arcuate fasciculus pathway is crucial for language, interconnecting posterior temporal and inferior frontal areas. Whether a monkey homolog exists was controversial and the nature of human-specific specialization unclear. Using monkey, ape and human auditory functional fields and diffusion MRI, we identified homologous pathways originating from auditory cortex. This discovery establishes a primate auditory prototype for the arcuate fasciculus, reveals an earlier phylogenetic origin and illuminates it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 30 publications
2
71
0
Order By: Relevance
“…The dorsal stream, which contains direct projections connecting posterior STG and lateral/inferior PFC (as well as indirect connections via posterior parietal cortex) in both species ( 27 ), harbors spatial as well as sensorimotor functions ( 17 ). On the basis of diffusion tensor imaging, it was found that the direct projection is denser and more left-lateralized in humans than in monkeys ( 66 , 67 ), but whether this quantitative difference can explain the qualitative difference in vocal production appears doubtful ( 68 ). Species differences in auditory–motor functions, including vocal behavior, are more likely to be found in the precise cross-stream coupling between ventral and dorsal streams ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal stream, which contains direct projections connecting posterior STG and lateral/inferior PFC (as well as indirect connections via posterior parietal cortex) in both species ( 27 ), harbors spatial as well as sensorimotor functions ( 17 ). On the basis of diffusion tensor imaging, it was found that the direct projection is denser and more left-lateralized in humans than in monkeys ( 66 , 67 ), but whether this quantitative difference can explain the qualitative difference in vocal production appears doubtful ( 68 ). Species differences in auditory–motor functions, including vocal behavior, are more likely to be found in the precise cross-stream coupling between ventral and dorsal streams ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…If categorisation is emergent in non-human primates and ubiquitous among modern humans, then parsimony points to the evolution of symbol use-and language-long before Homo sapiens. Pedersen (2012) concludes, following a study of the ability of captive bonobos to acquire visual and auditory symbols, that language evolved from deep-rooted semantic and conceptual abilities in the last common ancestor of chimpanzees and hominins, some six million years ago, and in recent work, it is argued that the neural, auditory pathway for language evolved at least 25 million years ago among monkeys (Balezeau et al 2020). The shared inheritance is based on biological and cognitive similarities in how humans and apes experience the world through their bodies and senses (Lakoff and Johnson 1999).…”
Section: Conventions and Categories Among Non-human Primatesmentioning
confidence: 99%
“…Human area 44 is interconnected with areas caudal to auditory cortex via the dorsal arcuate fasciculus pathway 13 . A recent comparative study showed a homolog of this dorsal auditory pathway in macaques 8 projecting from caudo-medial regions near to those that we electrically stimulated, which elicited vlPFC activity.…”
Section: Discussionmentioning
confidence: 68%
“…Left hemisphere areas posterior to Heschl’s gyrus (HG; an anatomical landmark associated with primary auditory cortex) are interconnected with Brodmann areas 44 and 45 in vlPFC by way of the dorsal arcuate fasciculus pathway 13 . There is now evidence for an auditory homolog in chimpanzees and macaques, with its left hemisphere lateralization as a prominent human-specific difference 8 . In monkeys, vlPFC neurons respond to vocalization sounds 14 , and single neuron tractography has shown evidence for directional connectivity between non-primary auditory (lateral belt) areas and vlPFC 15 .…”
Section: Introductionmentioning
confidence: 99%